2020
DOI: 10.18632/aging.103581
|View full text |Cite
|
Sign up to set email alerts
|

Early coagulation tests predict risk stratification and prognosis of COVID-19

Abstract: The ongoing outbreak of Coronavirus Disease 2019 (COVID-19) is hitting the world hard, but the relationship between coagulation disorders and COVID-19 is still not clear. This study aimed to explore whether early coagulation tests can predict risk stratification and prognosis. PubMed, Web of Science, Cochrane Library, and Scopus were searched electronically for relevant research studies published up to March 24, 2020, producing 24 articles for the final inclusion. The pooled standard mean difference (SMD) of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 68 publications
1
31
0
2
Order By: Relevance
“…Additionally, our study indicated that FDP was a risk factor associated with the development of critical COVID-19; more importantly, we identified that the AUROC of the FDP level was 0.71 with a cutoff of 0.95 µg/ml. These findings strengthen the suggestion that routine monitoring of coagulation parameters may represent a potentially useful tool to improve the early diagnosis of critical COVID-19 and establish an accurate therapeutic strategy 38 , 39 . It has been widely demonstrated that coagulation is activated and accelerated in response to infections because this mechanism may increase the physiological response 40 , 41 .…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, our study indicated that FDP was a risk factor associated with the development of critical COVID-19; more importantly, we identified that the AUROC of the FDP level was 0.71 with a cutoff of 0.95 µg/ml. These findings strengthen the suggestion that routine monitoring of coagulation parameters may represent a potentially useful tool to improve the early diagnosis of critical COVID-19 and establish an accurate therapeutic strategy 38 , 39 . It has been widely demonstrated that coagulation is activated and accelerated in response to infections because this mechanism may increase the physiological response 40 , 41 .…”
Section: Discussionsupporting
confidence: 81%
“…Urea and estimated glomerular filtration rate are important lab findings associated with an underlying chronic renal disease, which is a well-known predisposing factor of mortality [ 34 ]. In terms of the coagulation profile, COVID-19 generally presents a hypercoagulation state, thus resulting in an elevated prothrombin time and international normalized ratio in severe COVID-19 cases [ 3 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the condition of patients at high risk can rapidly deteriorate. Some papers reported that deceased COVID-19 patients initially had mild symptoms but suddenly transitioned to a critical stage, leading to death [ 3 - 5 ]. In Italy, 75% of deceased patients showed mild symptoms, such as fever, dyspnea, and cough, at admission to the hospital [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…1) D-dimers D-dimer elevation is a very common laboratory finding observed in COVID-19 patients, requiring hospitalization and predicting a poor prognosis [19] [42] [45] [46]. In fact, SARS-CoV-2 enters cells via ACE2 receptors, which are found in endothelial cells.…”
Section: Coagulopathymentioning
confidence: 99%